1998
DOI: 10.1002/(sici)1097-0185(199801)250:1<6::aid-ar2>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the rate of RNA synthesis during the cell cycle

Abstract: Cells synthesize RNA during the interphase, but at a variable rate with a peak in S. The synthesis proceeds in a majority of the cells at prophase, but only in a few of them at prometaphase and metaphase, and in none at anaphase and telophase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…The amount of rRNA in the cells exhibiting mitotic figures (Me 1 and Me 2 in Figures 3a, 3c, and 3e) markedly decreased. These results coincided with the changes in the rate of RNA synthesis during the cell cycle described in detail by Salem et al (1998). For examining the proliferative activity of cells, the use of histone mRNA is recommended because it degrades rapidly after S-phase is completed (Slowinski et al 2002).…”
Section: Rrna As a Positive Control For Ishsupporting
confidence: 56%
“…The amount of rRNA in the cells exhibiting mitotic figures (Me 1 and Me 2 in Figures 3a, 3c, and 3e) markedly decreased. These results coincided with the changes in the rate of RNA synthesis during the cell cycle described in detail by Salem et al (1998). For examining the proliferative activity of cells, the use of histone mRNA is recommended because it degrades rapidly after S-phase is completed (Slowinski et al 2002).…”
Section: Rrna As a Positive Control For Ishsupporting
confidence: 56%
“…Thereafter, in early G 1 , PUM2 might reassociate with the P2P‐R mRNA to again repress its translation. Future studies will have to evaluate this possibility, and future studies also will have to determine if high levels of P2P‐R influences transcription and translation control mechanisms that are known to be modified in mitotic cells (Salem et al, 1998; Sciortino et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The second discovery of the current research is that immunoreactive P2P‐R protein can be detected at > 10‐fold higher levels in mitotic cells than in G 0 cells using Western blotting techniques but that P2P‐R mRNA expression is not correspondingly increased. Confocal microscopy also showed that in mitotic cells, P2P‐R is localized to the periphery of chromosomes in mitotic cells that do not contain nucleoli and show markedly repressed RNA metabolism (Salem et al, 1998). Preliminary data using cells expressing transfected green fluorescent protein‐tagged P2P‐R also show the localization of P2P‐R at the periphery of mitotic chromosomes.…”
Section: Discussionmentioning
confidence: 99%